The Next Generation Is Here: A Review of Transcriptomic Approaches in Marine Ecology - Page, Tessa M.; Lawley, Jonathan W. (Frontiers in Marine Science, 2022)
As we enter the United Nations Decade of Ocean Science for Sustainable Development, extensive efforts to reverse the decline of ocean health are taking place. Moreover, the need to utilise innovative and integrative approaches to aid in these efforts and address marine ecological questions are urgent. Transcriptomic technologies provide tools to further our understanding of an organism’s biology by allowing researchers to rapidly gain information on the genetic variation of populations and the regulation of cellular processes and pathways through gene presence, absence, and expression. Here, we review the application of transcriptomics in the field of marine ecology over the last decade, following a systematic literature review approach. We found 478 articles that fit our search criteria of using transcriptomic approaches to address ecological hypotheses, with 70% of these studies occurring within the last 5 years. Among the analysed articles, 51.7% involved a type of stressor, 16.6% used transcriptomics to study adaptation, and another 15.9% researched ecological interactions. Most articles investigated species from kingdom Animalia, with a high representation from both molluscs (19.5%) and chordates (13.3%), and only 22% of studies had a fieldwork component. Our review demonstrates how the use of transcriptomic techniques in the field of marine ecology is increasing and how they are being applied. Although there are still challenges researchers experience using such techniques, particularly when annotating genes in non-model species and those with no prior genomic resources, these innovative technologies are extremely valuable in investigating differential gene expression, molecular pathways, and generating genomic resources.